1978
DOI: 10.1159/000237793
|View full text |Cite
|
Sign up to set email alerts
|

Absorption, Distribution and Elimination of Cefazolin in Patients with Normal Renal Function

Abstract: Cefazolin was given intramuscularly in a dosage of 1.0 g to 13 bed-ridden patients during treatment for various infections, and the pharmacokinetics evaluated in each subject. In 9 patients the mean serum half-life was 2.7 h, whereas in 4 patients – all over 60 years of age – it was significantly above this value. Impaired renal function could not explain the prolonged excretion time in the last group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1979
1979
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…However, the elderly patients had reduced renal function (mean creatinine clearance of approximately 50 mL/min), which most likely explains these findings. Studies on cefazolin and cephradine in a limited number of elderly subjects indicated prolonged serum half‐lives for both antibiotics, but renal function status of the patients were not reported 85 , 86 . Of the three oral preparations of first‐generation cephalosporins, i.e., cephalexin, cephradine, and cefadroxil, the latter agent has the advantage of increased serum half‐life and thus requiring dosing only every 12 hours 87 .…”
Section: Pharmacology and Pharmacokinetics Of Antibioticsmentioning
confidence: 99%
“…However, the elderly patients had reduced renal function (mean creatinine clearance of approximately 50 mL/min), which most likely explains these findings. Studies on cefazolin and cephradine in a limited number of elderly subjects indicated prolonged serum half‐lives for both antibiotics, but renal function status of the patients were not reported 85 , 86 . Of the three oral preparations of first‐generation cephalosporins, i.e., cephalexin, cephradine, and cefadroxil, the latter agent has the advantage of increased serum half‐life and thus requiring dosing only every 12 hours 87 .…”
Section: Pharmacology and Pharmacokinetics Of Antibioticsmentioning
confidence: 99%